Implementation Of Occupational Health And Safety Culture In Maintaining Zero Accident Stability For Workers In Sugar Factories - Ema Mayasari; Erina Esa Aisyarah; Tyas Wuryaningsih; Mohammad Saheri; Predito Prihantoro (Journal of Global Research in Public Health, 2024)
The application of occupational safety and health provides several benefits in every aspect of human life and provides benefits in every business activity and supports the progress of quality and sustainable development in the human resources, economic, social and environmental aspects. This research aims to find out and explore the application of occupational safety and health culture in maintaining zero accident stability. The informants in this research consisted of 4 main informants, namely installation workers, and 2 triangulation informants, namely occupational safety and health. The data analysis techniques used in this research are reduction, display and verification. Based on the research results, it was found that the implementation of occupational safety and health culture among production workers at the Sugar Factory where the research took place was classified as good and at an independent level, workers realized that work safety was a shared responsibility. Efforts to maintain zero accident stability include implementing good internal occupational safety and health communication, implementing discipline, monitoring and high work standards, and also in terms of investigating incidents the Company carries out quickly and responsively. However, during field observations, it was still found that workers were using incomplete PPE. The obstacle felt by workers and occupational safety and health parties is the return of PPE stock which sometimes takes a long time.